2018
DOI: 10.1007/s13402-018-0402-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic markers in basal cell carcinoma: universal themes in oncogenesis and tumor stratification? - a short report

Abstract: Our data reveal an EZH2-associated epigenetic marker profile that correlates with histologic signs of BCC aggressiveness. Our findings may have diagnostic and therapeutic implications, and indicate that epigenetic markers may be shared even with relatively less aggressive tumor types, thereby suggesting universal themes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…On the contrary, upregulated H3K27me3 and 5hmC were positively associated with a more benign phenotype. Finally, the authors were able to discriminate BCCs from non-malignant epidermal cells through the upregulated levels NSD2, MOF, H3K27me3, and 5hmC [124]. Harms et al investigated a series of MCCs and found that EZH2 was deregulated, inducing gene silencing via histone H3 lysine 27 trimethylation and was thus associated with unfavorable characteristics, such as disease progression and a poorer prognosis [117,125].…”
Section: Histone Methylation and Acetylationmentioning
confidence: 99%
“…On the contrary, upregulated H3K27me3 and 5hmC were positively associated with a more benign phenotype. Finally, the authors were able to discriminate BCCs from non-malignant epidermal cells through the upregulated levels NSD2, MOF, H3K27me3, and 5hmC [124]. Harms et al investigated a series of MCCs and found that EZH2 was deregulated, inducing gene silencing via histone H3 lysine 27 trimethylation and was thus associated with unfavorable characteristics, such as disease progression and a poorer prognosis [117,125].…”
Section: Histone Methylation and Acetylationmentioning
confidence: 99%
“…These data suggest that EZH2 may possess oncogenic functions in MPNST outside the context of PRC2, a phenomenon observed in other cancers. In many contexts, EZH2 expression negatively correlates with H3K27me3 levels but positively correlates with cancer cell proliferation and poor disease prognosis (121)(122)(123). There are also numerous examples of specific noncanonical EZH2 targets and interactions that drive tumor development and metastasis.…”
Section: Loss Of Prc2 In Mpnstmentioning
confidence: 99%
“…Finally, one recent study reported the association between advanced BCC and the histone methyltransferase EZH2 [ 94 , 95 ]. First, the authors tested the expression levels of EZH2 and the proliferation marker Ki67 in 30 cases of less aggressive BCC histologic subtypes and 30 cases of more aggressive histologic subtypes (morpheaform, infiltrative, and micronodular).…”
Section: Histone Methylation: Highly Mutated Modifiers In Kcsmentioning
confidence: 99%
“…EZH2 and Ki67 expression were significantly increased in the more aggressive BCCs as compared to that of the less aggressive BCCs, and positively correlated with the aggressiveness of BCC. They suggested that EZH2 may be a potential target to inhibit BCC progression [ 95 ]. In follow-up work, they tested the expression levels of H3K27me3, 5hmC, NSD2, MOF, JARID1B, EZH2, and Ki67 from the same BCC patients that they examined in the previous study, as well as matched non-malignant normal epidermal tissue to further explore the relationship of epigenetic modifiers to BCC.…”
Section: Histone Methylation: Highly Mutated Modifiers In Kcsmentioning
confidence: 99%